PERMINTAAN UANG DI INDONESIA : ANALISIS VARIABEL MAKRO EKONOMI - N Istikomah; A.D Kusuma; K. Y Khairunnisa; M.D Ghifari (Jurnal Pendidikan Ekonomi Indonesia, 2020)
This research is motivated by economic instability caused by the instability of monetary factors in Indonesia, especially the condition of the money supply in Indonesia. This study aims to determine the effect of interest rates, economic growth and inflation on the demand for money which is proxies by the Money Supply (M2). This study uses a quantitative approach. The type of data used is secondary data from 2000 to 2020. The results obtained in the study were analyzed using the least squares method of Multiple Linear Regression analysis using the SPSS program. The test results based on the significance of the t test states that interest rates have a positive effect, economic growth has a negative effect and inflation has no positive effect on the Money Supply. Then, based on the significance of the f test of Interest Rates, Economic Growth and Inflation simultaneously (simultaneously) affect the Money Supply.